MENINGKATKAN KREATIFITAS SISWA MELALUI KETERAMPILAN MELUKIS POTRET MENGGUNAKAN MEDIA PENSIL KORAN PADA PELAJARAN SENI BUDAYA - Witarsa, Enjang (Universitas Pendidikan Indonesia, 2016)
Portrait painting skills competency is the ability of learners in expressing themselves creatively through various means and media to take advantage of the language. Methods used namely research action class. Primary data collected from observation sheets practice regular learning, learning cycles, the cycle I and cycle II, III, the data analyzed by quantitative approach. While secondary data collected from observations observer, the now and the self-reflection of researchers, this data is analyzed with a qualitative approach. Results of the study illustrate that using Pencil media newspaper effect on increasing the skills of painting portraits. This is reflected in a significant way from the average value of test results practice cycles I = 2.61, cycle II = 2.76, and cycle III = 3.10, as well as the learning achievements of students gain (gain score) of 1.00. The interpretation of the question form responses to learners against media newspaper pencil was 84% (a little under very strong) meaning that paint a portrait using pencil paper making learners learning more active, creative, and fun.